Radionuclides Activity and Radiological Hazard Assessment in Bananas Samples Exported to Iraq - Al-Juboury , Basim Kh.; Ali, Akram M. (Iraqi Journal of Science, 2022)
The average concentration of radionuclide’s in the various banana samples were collected from being the most popular markets in Baghdad city - Iraq were measured by use Sodium Iodide Thallium [NaI(Tl)] detector. The radionuclide’s observed with reliable regularity belonged to the series-decay naturally occurring radionuclide’s headed by 232U and 232Th as well as the non-series nuclide, 40K and 137Cs. The average concentration of 40K was found the least average concentration value recorded as876.74625Bq kg-1.The average concentration of 238U was 28.6425Bqkg-1for ²³²Th, it was found to have the average concentration 14.1805 Bqkg-1. The cesium concentration in the sample was found in the healthy range.